V8SiB4 — A new ternary phase in the V–Si–B system. (December 2022) - Yang, W.G.; Touzani, R.S.; Hasemann, G.; Yazlak, M.; Ziegner, M.; Gorr, B.; Schwaiger, R.; Krüger, M.
Abstract: The present study reports on the existence of a new ternary phase, V8 SiB4, in the V–Si–B system. The new phase was found in alloys heat-treated at 1400 °C for 100 h and 200 h within the Vss –V3 Si–V5 SiB2 phase field at 1600 °C. The crystal structure of V8 SiB4 was determined by combining energy-dispersive X-ray spectroscopy (EDS), X-ray diffraction (XRD) and density functional theory (DFT) calculations. To further examine the stability of V8 SiB4, electronic density-of-states (EDOS), phononic density-of-states (PDOS), the chemical bonding and the elastic properties of V8 SiB4 were calculated using DFT and compared with the properties of V5 SiB2 (T2). Highlights: A new ternary phase, V8 SiB4, was found in the Vss -V3 Si–V5 SiB2 phase region at 1600 °C after heat treatment at 1400 °C for 100 h and 200 h. By combining EDS, XRD and DFT calculations, we determined the crystal structure of V8 SiB4, which may represent a new crystallographic prototype. The stability of V8 SiB4 at 0 K was examined using DFT.